PROTECTIVE ROLE OF XINNAONING TABLET IN ISCHEMIC STROKE IN RAT MODEL - Wang, Ling; Lv, Hongdi; Xie, Guoqi; Su, Feng; Geng, Xiuli; Hao, Shaojun; Zhang, Zhengchen (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Stroke has been considered as the second leading cause of death worldwide. The survivors of stroke experience different level of impair brain function. In China, Chinese traditional medicine had been widely accepted for stroke therapy and prevention. In this study, we developed Traditional Chinese Medicine based Xinnaoning (peace of heart and brain) Tablet and tested its protective role for ischemic stroke in rat model. Material and Methods: Male Wistar rats (n=60) with 12 weeks old and weight from 180 to 200 gram were randomly divided to five groups (n=12). For the groups with Xinaoning administration, the drug was administrated to rats once per day for 7 consecutive days. The blood clotting time and the thrombus wet weight was measured. Serum samples were collected from each rat for further Measurement of biochemical indicators. Results: Our results demonstrated that Xinnaoning tablet reduced lactate acid (LD) level and increased lactic acid dehydrogenase (LDH) in cerebral ischemia model as well as reduced the infarct size caused by stroke. Besides, evaluation of the level of different ATPases suggested Xinnaoning tablet could modulate ATPases activity and confer a protective role in brain. Moreover, analysis indicated Xinnaoning tablet have the anti-coagulation effect in vivo which may contribute to the protection of ischemia. Conclusion: Our findings suggest that Xinnaoning tablet may be a potential way for cerebral ischemia prevention.